Loon : memory, meaning, and reality in a northern Dene community - Sharp, Henry S. (University of Nebraska Press, 2001)
In August 1975 at Foxholm Lake on the reserve of the Chipewyan, a Northern Dene people, in the Northwest Territories of Canada, the anthropologist Henry S. Sharp and two members of the Mission Band encountered a loon. Loons are prized for their meat and skin, so the two Chipewyan tried-thirty times-to kill it. The loon, in a brazen display of power, thwarted these attempts and in doing so revealed itself to be a "spirit." In this book, Sharp embarks on a narrative exploration of the Chipewyan culture that examines the nature of a reality within which wild animals are both persons and spirits. In an unforgettable journey through the symbolic universe and daily life of the Chipewyan of Mission, his work uses the context and meaning of the loon encounter to show how spirits are an actual and almost omnipresent aspect of life